The Development of a Group Counseling Program to Enhance Academic Achievement Motivation of Vocational Students in Three Southern Provinces of Thailand - Kongpaen, Wannee; Punthai, Boonmee; Suriyasasin, Srismorn (Ph.D. in Social Sciences Journal, 2024)
This research article aims to develops and examines the effectiveness of a group counseling program to enhance the academic achievement motivation of the vocational students in three southern provinces of Thailand. In this quasi-experimental research, the sample population consisted of thirty-two students at Pattani Technical College at the Vocational Certificate. The research instruments consisted of the following: (1) a group counseling program to enhance the academic achievement motivation; and (2) an academic achievement motivation test. The hypothesis test was conducted using non-parametric statistics of the Sign Test and the Wilcoxon-Mann-Whitney Test. Findings are as follows: (1) The group counseling program to enhance the academic achievement motivation of the vocational students under study consisted of four stages: the initial stage; the transition stage; the working stage; and the final stage. The program was conducted for twelve times for one and a half hours per time. (2) The constructed program exhibited the effectiveness on the academic achievement motivation of the students under investigation. The students in the experimental groups exhibited a higher level of academic achievement motivation after participating in the group counseling program than prior to their participation in the program. They exhibited academic achievement motivation at a higher level than the control groups at the statistically significant level of .05. After the follow-up period of four weeks, the experimental groups exhibited retention of the academic achievement motivation. It was also found that the students at the two levels who were in the experimental groups exhibited no differences in their academic achievement motivation after participating in the program.